2012
DOI: 10.4236/jbbs.2012.23041
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Suppresses the Electroencephalographic Response to Visual Erotic Stimuli in Young Men

Abstract: Although the combination of alcohol and sex is frequently observed in human social interaction, many questions concerning alcohol's effects on the processing of sexual stimuli and brain functionality remain unanswered. Erotic films eliciting sexual arousal in humans and affect electroencephalographic (EEG) activity. This study examines the effects of alcohol on cortical EEG activity in young men while viewing an erotic film. Heterosexual males participated in an independent alcohol/placebo group protocol. Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Other studies have shown the role of the prefrontal cortex in the motivational aspects of motor performance and sexual behavior [30,32] and there is also evidence that this structure is involved in the processing of stimuli of potential incentives to generate sexual arousal and motivation (for a review, see [5]). In studies with humans, it has been also demonstrated that ethanol affects the functioning of the prefrontal cortex, which has been suggested that it could interfere with the adequate processing of visual erotic stimuli [11]. Thus, it is likely that in this study the ethanol could affect the proper functioning of this cortical area, decreasing the degree of coupling or synchronization with the parietal cortex.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Other studies have shown the role of the prefrontal cortex in the motivational aspects of motor performance and sexual behavior [30,32] and there is also evidence that this structure is involved in the processing of stimuli of potential incentives to generate sexual arousal and motivation (for a review, see [5]). In studies with humans, it has been also demonstrated that ethanol affects the functioning of the prefrontal cortex, which has been suggested that it could interfere with the adequate processing of visual erotic stimuli [11]. Thus, it is likely that in this study the ethanol could affect the proper functioning of this cortical area, decreasing the degree of coupling or synchronization with the parietal cortex.…”
Section: Discussionmentioning
confidence: 68%
“…The changes occurring in regions such as the hippocampus or in the neocortex are particularly important because they are structures involved in modulating motivated behaviors, such as sexual behavior [4,5] as well as processes such as attention, memory and executive processes, which are affected by ethanol [6]. In fact, a high percentage of alcoholics demonstrates significant sexual [7,8] and neuropsychological dysfunctions [9,10] and some results with EEG recording have shown that ethanol induces important changes in the functionality of the PFC and Parietal Cortex during sexual arousal [11] and cognitive tasks [12]. In rats similar alterations occur, so that after the ethanol administration (1 g/kg) increased, rodent sexual motivation but impaired specific parameters of sexual performance has been reported [13]; moreover, increases in the activity of dopaminergic neurons of the ventral tegmental area (VTA) that result in an increase in the levels of dopamine primarily in the shell of the nucleus accumbens (Acc) [14,15] in a dose-dependent manner [16][17][18][19][20][21] have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%